Structural, magnetic phase stability, and electronic properties of Co₂RuSb Heusler compound - Khatri, Prakash; Adhikari, N. P. (BIBECHANA, 2026)
The properties of Co₂RuSb were studied using DFT with the PBE-GGA functional for exchange correlation energy. The most stable structures are identified by examining four distinct atomic configurations: L2₁-I, L2₁-II, XA-I, XA-II configurations. Phase stability analysis in these configurations reveals that the ferromagnetic (FM) phase is more favorable than the antiferromagnetic (AFM) and nonmagnetic (NM) phases. Among all the considered structural and magnetic configurations, the compound prefers the XA-I type structure with a ferromagnetic (FM) ground state. The phonon dispersion curve, showing no imaginary frequencies, indicates that the Co₂RuSb compound is dynamically stable. From Born's stability criteria for elastic constants, Co₂RuSb is mechanically stable, exhibiting ductile behavior, and possess high melting temperatures. The spin polarized band structures calculated with GGA reveal metallic behavior for both spin channels. The inclusion of on-site Coulomb interaction (U) via GGA + U might open the band gap in Co₂RuSb, making it potentially valuable for spintronic applications.